A Cockroach Egg Parasitoid, Evania appendigaster (Linnaeus) (Hymenoptera: Evaniidae) - Lionel Stange (EDIS, 2006)
This document provides an in-depth profile of the cockroach egg parasitoid, Evania appendigaster (Linnaeus), detailing its identification, distribution, biology, and potential for biological control. Originating from the Orient, this wasp is now widespread in tropical and subtropical regions. It parasitizes cockroach egg cases, with the female inserting her ovipositor into the egg case to lay a single egg. The developing larva consumes all the cockroach eggs within the case. The document also discusses the wasp's competitors and its potential effectiveness in controlling cockroach populations.